Auditor Reputation, Auditor Independence, and the Stock‐Market Impact of Andersen's Indictment on Its Client Firms* - Krishnamurthy, Srinivasan; Zhou, Jian; Zhou, Nan (Contemporary Accounting Research, 2006)
In this paper, we study a broad sample of Arthur Andersen clients and investigate whether the decline in Andersen's reputation, due to its criminal indictment on March 14, 2002, adversely affected the stock market's perception of its audit quality. Because these reputa‐tional concerns are more of an issue if an auditor's independence is impaired, we investigate the relationship between the abnormal market returns for Andersen clients around the time of the indictment announcement and several fee‐based measures of auditor independence. Our results suggest that when news about Andersen's indictment was released, the market reacted negatively to Andersen clients. More importantly, we find that the indictment period abnormal return is significantly more negative when the market perceived the auditor's independence to be threatened. We also examine the abnormal returns when firms announced the dismissal of Andersen as an auditor. Consistent with the audit quality explanation, we document that when firms quickly dismissed Andersen, the announcement returns are significantly higher when firms switched to a Big 4 auditor than when they either switched to non‐Big 4 auditors or did not announce the identity of the replacement auditor. Our empirical results support the notion that auditor reputation and independence have a material impact on perceived audit quality and the credibility of audited financial statements, and that the market prices this.